Penterjemahan simpulan bahasa Arab-Melayu: satu analisis teori relevans - Jumingan, Muhammad Fauzi (Universiti Putra Malaysia Press, 2004)
At the end of the twentieth century, theories and approaches were introduced in the field of translation. Amongst these theories were dynamic theory by Nida and Taber (1967), semantic and communication theory by Newmark (1981), scopos theory by Vermeer and Reis (1981), and literature theory by Larson (1984). Basically, all of these theories have been more focused on the product of translation. There was also a new theory of translation that was proposed in the field of human communication. Actually, this theory had rejected the old concept of communication that was based on the system of coding-transmission-decoding. In other words, based on this new theory, the process of communication must involve the process of the human mind. Later on, this process would make a decision on communication. This theory was named the Relevance Theory (TR) that was developed by Sperber and Wilson (1986/1995). After that, TR was developed by Gutt in the field of translation. This article will discuss the application of TR in the Arabic-Malay translation. How the concept of two meanings operated and which one is the real meaning will be answered by TR.